On the syntaxonomic position of Festuco-Limonietea Karpov et Mirkin 1986 in Ukraine (CHORNOMORSKI BOTANICAL JOURNAL, 2007)
Revision of Festuco-Limonietea syntaxa in Ukraine is given. Author’s coenotic analysis shows that the class Festuco-Limonietea is a syntaxonomic synonym of Festuco- Puccinellietea. Due to its dominants and edificators, Festuco-Limonietea syntaxa belong to other classes of the steppe vegetation in Ukraine – Festuco-Brometea, Festuco- Puccinellietea, Agropyretea repentis, Salicornietea fruticosae. Syntaxonomic structure of the class Festuco-Puccinellietea is discussed.
Keywords: syntaxonomy, Festuco-Limonietea, Festuco-Puccinellietea, coenotic analysis, revision.